PELATIHAN AKUNTAN, KINERJA AKUNTAN DAN TEKNOLOGI INFORMASI SEBAGAI DETERMINAN KUALITAS INFORMASI AKUNTANSI - Rochman Marota; Monica Ani Lestari; Amelia Rahmi (Universitas Pakuan, 2020)
The purpose of this study was to determine the effect of accountant training, accountant performance and information technology on the quality of accounting information on the BOS (direct fund assistance) reports for SMK (vocational high school) in Bogor City. The research method used is quantitative research methods. The population in this study were BOS treasurers at SMK in Bogor City. The sampling technique used purposive sampling method and the research sample obtained was 41 respondents from 20 private vocational schools in Bogor City. The hypothesis analysis method used is multiple linear regression. The results of this study indicate that accountant training, accountant performance and information technology simultaneously and partially affect the quality of accounting information. The variable that has the highest influence is information technology with the highest tcount, meaning that the quality of accounting information is more driven by information technology. The implication of this research is that vocational secondary education providers can build or improve information technology to help better present financial reports apart from developing the quality of accountants.